BILATERAL CLAVICLE FRACTURES TREATED WITH SCREW INTRAMEDULLARY FLEXIBLE NAIL - Choudhury, Priyam; Mohapatra, Ashutosh; Gadegone, Piyush; Gadegone, Wasudeo; Mohapatra, Rabinarayan (Journal of Ayub Medical College Abbottabad, 2022)
Clavicle fractures have been known to be common injuries with a reported incidence of 2.4-4% amongst all fractures, however the incidence of bilateral clavicle fractures is rare. A thorough search of all English language journals revealed that bilateral clavicle fractures comprised 0.43% of all clavicle fractures, with an overall incidence of between 0.011-0.017%. Though the surgical intervention of clavicle fractures uses many implants, never has been screw intramedullary flexible nail been used in a bilateral clavicle fracture. We report a case of a 32-year-old male who presented with bilateral clavicle fracture and was treated successfully. Keywords: Bilateral clavicle fractures, closed reduction, internal fixation, intramedullary